Debus dalam Pandangan Masyarakat Buddha di Wilayah Banten Kota Serang (Studi Kasus Umat Buddha di Vihara Avalokitesvara) - Yanti Pradila; Muhamad Tamamul Iman (Inklusiva: Jurnal Studi Agama-Agama, 2024)
This research discusses how Buddhists view culture in Banten, one of which is Debus Art and examines the role and social function of Debus in the Old Banten area. This research shows that in the teachings of Buddhism not to commit violence and not harm other people nor injure yourself. In this attraction, Debus performs his attraction using violence or immunity using sharp objects. This is the reason why Debus is related to Buddhist teachings which know the teachings of Ahimsa Love and Love. The results of this research show the views of non-Muslim communities towards Debus, that there are several opinions from Buddhists who reject Debus attractions that use the body's immunity or simply accept the existence of art in Banten as recognition of Debus as one of Banten's cultures. In the past, Debus functioned as a means to spread Islamic teachings, but then it developed into use as a medium to pump up the enthusiasm of the people of Banten in facing Dutch colonialism during the reign of Sultan Ageng Tirtayasa.